2010
DOI: 10.1002/ijc.25444
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes based on treatment algorithms for rhabdomyosarcoma of the bladder/prostate: Combined results from the Children's Oncology Group, German Cooperative Soft Tissue Sarcoma Study, Italian Cooperative Group, and International Society of Pediatric Oncology Malignant Mesenchymal Tumors Committee

Abstract: The purpose of this study was to determine patient characteristics and outcomes for bladder/prostate (BP) rhabdomyosarcoma (RMS) using an international cohort of prospectively treated patients comparing different treatment algorithms. Data were collected from 379 patients (1979-1998) treated on protocol; Intergroup Rhabdomyosarcoma Study, IRS-IV (n 5 239 patients), International Society of Pediatric Oncology Malignant Mesenchymal Tumors (MMT) Committee MMT-84 and -89 (n 5 74), Italian Cooperative Group, RMS-79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 44 publications
3
71
0
Order By: Relevance
“…Moreover, there was significant association between risk groups and 4-year PFS and OS rates: patients with LR and IR group had better outcomes than those with HR diseases, which is consistent with results reported by collaborative groups on RMS [9,15,[18][19][20][21][22][23][24]. Seven (16%) patients had alveolar histology, which was lower than expected as population-based estimates of alveolar histology are around one third of all tumors; however, our study sample is small and it is hard to draw any conclusion from this finding.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there was significant association between risk groups and 4-year PFS and OS rates: patients with LR and IR group had better outcomes than those with HR diseases, which is consistent with results reported by collaborative groups on RMS [9,15,[18][19][20][21][22][23][24]. Seven (16%) patients had alveolar histology, which was lower than expected as population-based estimates of alveolar histology are around one third of all tumors; however, our study sample is small and it is hard to draw any conclusion from this finding.…”
Section: Discussionsupporting
confidence: 89%
“…24 Patients with localized alveolar histology fared worse than patients with localized embryonal histology, but this subtype was much less common (5year OS of 47%, n = 21). Among patients with metastatic bladder or pros tate rhabdomyosarcoma (n = 36), 5year OS was only 44%.…”
Section: Rhabdomyosarcomamentioning
confidence: 91%
“…5 This is probably a result of the aggressive radiotherapy for local tumor control in the IRS trial. 5 Overall surgical approach advocates tumor excision at the time of diagnosis only, if it is possible without causing major functional deficits or cosmetic sequelae. Initial biopsy of the tumor represents the best option for most B/P RMS, although very few authors suggested debulking surgery for tumors that could not be completely excised before chemotherapy.…”
Section: Treatmentmentioning
confidence: 99%
“…This may be a biased observation since recent data analysis suggests that the COG and SIOP approaches attain similar EFS when the stage and size of the tumors are properly matched. 5 It needs to be underlined that not only short-term survival rates and local tumor control but also long-term complications, bladder function, and toxicity must be considered when comparing different therapeutic strategies. For cancer survivors, bladder and sexual function, as well as management and treatment of complications, gain increasing importance, although data of late functional effects of survivors are still limited.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation